Influence of menopause on endodontic treatment - Gomes-Filho, João Eduardo [UNESP]; Martins, Christine Men [UNESP]; Sivieri-Araujo, Gustavo [UNESP]; Santos, Ludmilla Mota da Silva [UNESP]; Queiroz, índia Olinta de Azevedo [UNESP]; Wayama, Marcelo Tadahiro [UNESP]; Yamanari, Guilherme Hiroshi; Dezan-Júnior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo (Dental Press International, 2014)
Menopause is one of the physiological changes characterized by the end of menstrual and ovulatory cycles occuring in women in their fourth and fifth decade of life. Thereat, production of estrogen, an important hormone that acts in many physiological process of the individual such as the regulation of skeletal system, decreases. The decline in estrogen levels results in loss of bone mineral density, increased fracture risk, as well as bone diseases such as osteoporosis, a pathological process in which there is increased resorption of cavities that are not completely filled by newly formed bone. Furthermore, estrogen deficiency can cause many changes in an individual's oral health. In the presence of bacterial infection of pulp tissue, this deficiency can aggravate apical periodontitis. Several drugs have been studied as potential therapeutic agents to compensate for deficiency of estrogen. These drugs aim to reduce the likelihood of fractures and prevent bone loss as well as cardiovascular and mental disorders resulting from postmenopausal hormone disabilities. Raloxifene (RLX) is one of the most studied drugs therapies and proves to prevent bone loss. Even though raloxifene is indicated for and produces benefits to bone metabolism and maintenance of bone density, additional studies are warranted to further investigate the role of raloxifene in endodontic infection of osteopenic organisms.
Keywords: Endodontics; Menopause; Systemic diseases